Encyclopedia of Philippine folk beliefs and customs - Demetrio, Francisco R.; Panis, Marcelino C. (Xavier University, 1991)
This 1990 edition is the revised and enlarged edition of the Dictionary of Philippine Folk Beliefs and Customs, which was published in four small volumes in 1970. This two-volume encyclopedia covers published works of folk beliefs and customs from 1967 to 1987. It is composed of twenty five chapters concerning topics about action, amulets and talismans, prayers, aswangs and witches, birth, death, directions, diseases and sickness, engkantos and spirits, beasts and celebrations, folk medicine, games and pastimes, marriage, natural phenomena, sacrifice and rituals, and weaponry.